Категория рода русских существительных в гендерном аспекте: парадигматический и синтагматический потенциал - Łuczyk, Małgorzata; Панова, Галина (Acta Neophilologica, 2019)
This article proposes a gender classification of Russian declinable nouns. The following aspects are discussed:1. The way in which nouns are connected with gender semantics: factually, when the gender stem is part of their lexical meaning structure, or potentially;2. the level at which the semantics is rendered: the level of the word (within the lexeme stem or the entire word form) or the level of the syntagma;3. the semantic nature: the meaning of the biological or the symbolic gender that is present in the anthropomorphic reflection of the world.